Integration of persuasive multimedia in designing learning application for child sexual abuse - Othman, Azliza; Wan Yahaya, Wan Ahmad Jaafar; Muniandy, Balakrisnan (UTM Press, 2015)
This paper focuses on the design of learning application with the purpose to provide knowledge on child sexual abuse (CSA) to children ages 7 to 9 years old. Currently, children are not aware of prohibited adult touches to their body due to lack of knowledge on CSA.Moreover, information on how to avoid potential of CSA and self protection is still lacking.In such situation, they need to be educated and made aware of the danger of sexual abuse.In providing a better learning aid, this study incorporates multimedia learning and persuasive technology in developing a learning application named Persuasive Multimedia Learning Application (PMLA).Additionally, this study also adopts the components in constructivist learning environment (CLE) for the organization of the contents in designing PMLA.Then, perceived motivation test was conducted to assess children’s learning experience after using the application. The results show that the integration of multimedia and persuasive technology has potential in motivating children in using the application and facilitating them for better understanding on CSA.